Analysis Of Murabahah And Mudharabah Financing On Net Profit At Bank Muamalat Indonesia Period 2017-2021 - Ananda, Fitri; Nasution, R (Peneliti.net, 2024)
This study aims to determine the effect of murabahah and mudharabah financing on the net profit of Bank Muamalat Indonesia for the period 2017-2021. The data analysis method used is quantitative descriptive verification. Five sample periods from 2017 to 2021 at Bank Muamalat Indonesia are used in this study. The findings show that (1) murabahah financing has a partial impact on net income, (2) mudharabah financing has no partial impact on net income, and (3) murabahah and mudharabah financing have a significant effect on net income simultaneously.